PERAN KADER POSYANDU DALAM PENCEGAHAN STUNTING DI DESA DUKUHSARI KECAMATAN JABON KABUPATEN SIDOARJO - Dila Dwi Andayani; Ilmi Usrotin Choiriyah (Halu Oleo University, 2025)
This study aims to identify the role of posyandu cadres in stunting prevention efforts in Dukuhsari Village, Candi District, Sidoarjo Regency. This study is based on a qualitative descriptive approach with observation and interview methods and utilizes primary and secondary data. Stunting is a chronic nutritional problem associated with malnutrition due to minimal nutrient absorption in the long term, as explained by Fatimah (2021). Stunting conditions are often difficult for the community to recognize due to the lack of attention paid to the growth and nutritional development of toddlers. Research in Dukuhsari Village shows that posyandu cadres deliver stunting information very effectively through face-to-face meetings. Although posyandu facilities are adequate, cadre training and fundraising are needed. Government support, participation of mothers of toddlers, and involvement of health workers are important for the success of stunting prevention so that posyandu cadres are more active and enthusiastic in carrying out their duties.